L'évolution du champ scolaire au Burkina Faso : entre diversification et privatisation - Marc Pilon (Les éditions de la Maison des sciences de l'Homme, 2004)
The comparison of the trends in the public and private sectors in both primary and secondary levels in Burkina show that the educational field has significantly changed since the country's independence four decades ago. The educational sector has diversified and become more complex. The market share and composition of the private sector varies substantially according to the educational level and place of residence. The ten year education development plan, launched in 2001, predicts a further increase of the private sector. This raises a number of issues for the coming years. What type of balance between the private and public sectors is best suited for the country? What type of private school for what type of education, and for whom? As increased diversification implies a process of privatization, how can its negative effects on social inequities in education be contained?